IMPROVING STUDENTS’ ACHIEVEMENT MOTIVATION THROUGH ROLEPLAY - Amir, Mochamad Abdul Azis; Rachmaniar, Ananda; Rismayadi, Hendri; Julius, Andre (iora, 2020)
The background of the study is the low achievement motivation of the studentsin which they are unable to show their potential optimally. Thisstudy aims to increase the students’achievementmotivation throughroleplay. The study employed a quasi-experimental method with a nonequivalent (pretest and posttest) control group design. The participants of the study were the grade X students ofSMAN 6 Bandung in academic year 2019/2020. The result shows that students’ achievement motivation is increased through role play. Role playtechniqueis able to provide changes in the students’ attitudes which are supported by the results of the assessment conducted on selected students as assessors.